Analisis Faktor-Faktor Yang Mempengaruhi Perataan Laba (Studi pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia) - Susanti, Sufiyati (Jurnal Paradigma Akuntansi, 2021)
This research aims at how the effect of profitability, financial leverage, net profit margin, liquidity, and firm size toward income smoothing on consumer goods industry listed on the Indonesia Stock Exchange during 2017-2019. Sample was selected using purposive sampling method and there was 35 companies been analyzed. Data processing techniques using binary logistic regression analysis what helped by Eviews 10 and Microsoft Excel 2019. The results of this study indicate that profitability, financial leverage, net profit margin, liquidity, and firm size didn’t have significant influence on income smoothing. The implication of this study is financial ratios that analyzed in this study and firm size can’t be used as indicator for investors to determine whether a company have income smoothing.